Value chain transformations in the transition to a sustainable bioeconomy - Pablo Mac Clay; Jorge Luis Sellare (University of Bonn, Center for Development Research (ZEF), 2022)
The adoption of new bio-based technologies that reduce our reliance on fossil fuels is presented as a path to reduce greenhouse gas emissions while creating new business opportunities. Such a transition towards a bio-based economy will require substantial investments in technological innovations that will likely affect how value chains are structured and which actors benefit from this transformation. Yet, previous studies on the bioeconomy have largely ignored the relationship between the structure of value chains and the rate of technological innovation. In this article, we analyze the link between technological innovation, value chain structures, and welfare distribution in the transition to a bioeconomy. We find that an acceleration in the rate of bioeconomy innovation is associated with shorter and more vertically coordinated value chains, bigger firms with higher market shares, increasing knowledge-sharing among value chain members, and a leading role by firms with core research capabilities. Finally, we argue that while bio-based innovation can potentially achieve environmental sustainability, it creates risks for the weakest value chain actors. Thus, we propose some lines of thought regarding the potential distributional effects of bio-based innovation. From a policy perspective, this debate is relevant to safeguarding social sustainability in the transition to a bioeconomy.
Keywords: 330; bioeconomy; innovation; upgrading; value chains; welfare